Panama Canal (2014)
In the 16th century, the idea of ​​building a navigation channel that linked the Atlantic and the Pacific to the narrowest place between the two oceans began: the isthmus of Panama. Separated by a little more 80 kilometers, the canal would replace nothing less than the long cruise on the southern tip of the continent, while its contribution to world trade would be enormous.